The homeobox transcription factor HOXA9 is a regulator of SHOX in U2OS cells and chicken micromass cultures. - Claudia Durand; Eva Decker; Ralph Roeth; Katja U Schneider; Gudrun Rappold (PLoS ONE, 2012)
The homeobox gene SHOX encodes for a transcription factor that plays an important role during limb development. Mutations or deletions of SHOX in humans cause short stature in Turner, Langer and Leri-Weill syndrome as well as idiopathic short stature. During embryonic development, SHOX is expressed in a complex spatio-temporal pattern that requires the presence of specific regulatory mechanisms. Up to now, it was known that SHOX is regulated by two upstream promoters and several enhancers on either side of the gene, but no regulators have been identified that can activate or repress the transcription of SHOX by binding to these regulatory elements. We have now identified the homeodomain protein HOXA9 as a positive regulator of SHOX expression in U2OS cells. Using luciferase assays, chromatin immunoprecipitation and electrophoretic mobility shift assays, we could narrow down the HOXA9 binding site to two AT-rich sequences of 31 bp within the SHOX promoter 2. Virus-induced Hoxa9 overexpression in a chicken micromass model validated the regulation of Shox by Hoxa9 (negative regulation). As Hoxa9 and Shox are both expressed in overlapping regions of the developing limb buds, a regulatory relationship of Hoxa9 and Shox during the process of limb development can be assumed.